The Role of the College Student Teaching Supervisor in In-Service Teacher Education - Johnson, James A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This paper describes the traditional role of the college student teaching supervisor, makes some observations concerning this role, and suggests a new role. The author makes the following observations about the traditional role: (a) it implies that the college supervisor can best contribute to teacher education by observing and then holding conferences with student teachers; (b) it has frustrated college supervisors, student teachers, supervising teachers, and administrators because it does not meet their needs and expectations; (c) it makes it impossible for the best college supervisors to make a substantial contribution to student teachers; and (d) it is a waste of the college supervisor's talents. The author recommends a new role that would involve decreasing the amount of time devoted to observing and holding conferences with student teachers and increasing the amount of time devoted to in-service teacher education. Four advantages of this new role are listed. It is suggested that this new role will improve in-service teacher education since college supervisors constitute a group that is well qualified and conveniently available to improve in-service teacher education. Seven cautions regarding the new role of college supervisors are described at the conclusion of the paper. A 10-item bibliography is included. (PD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Inservice Teacher Education; Staff Role; Student Teacher Supervisors; Student Teaching; Teacher Role; Reports, Research